218 Using Mini-Jupette Slings to Treat Post Radical Prostatectomy Urinary Incontinence: Foreplay Incontinence, Climacturia, and Stress Incontinence. (1st May 2022) - Brady, J; Choi, E; Foley, B; Wilson, S; Yafi, F
ABSTRACT: Introduction and Objective: The Mini-Jupette has been successfully used concomitantly with inflatable penile prostheses (IPP) to treat erectile dysfunction (ED), climacturia and stress urinary incontinence (SUI) secondary to radical prostatectomy (RP). This is the largest single surgeon report of the original Andrianne Mini-Jupette sling and IPP placements in men with ED and climacturia, mild SUI and/or foreplay incontinence. Methods: This was a retrospective study on a prospectively managed database of 32 patients who underwent IPP and Mini-Jupette placement using Tutoplast® cadaver pericardium graft by a single surgeon between July 2016 and February 2020. Patients were surveyed pre- and post-operatively and asked to score the severity of their foreplay incontinence (FI), climacturia, and SUI from 0 ("dry"), 1 ("1 drop"), 2 ("few drops"), 3 ("small dribble"), or 4 ("squirt of urine"). Patient surveys were compared pre- to post-operation using Fisher's exact test. Results: Of the 32 men, 27 (84%) had FI, 26 (81%) with climacturia, and 27 (27%) with SUI (Table 1). At a mean follow-up of 17.9 months, FI (p<0.001), climacturia (p<0.001), and SUI (p<0.001) all significantly improved (Table 2). FI improved in 78.9% (15/19) and resolved in 47.4% (9/19); climacturia improved in 82.3% (14/17) and resolved in 64.7% (11/17); SUI improved in 71.4% (15/21) and resolved in 57.1% (12/21). Sexual Health Inventory for Men (SHIM) scores significantly improved from 5.0 to 23.8 (p<0.001) for the entire group. Three patients (9.4%) required an artificial urethral sphincter (AUS) for the management of persistent incontinence. One patient underwent IPP revision due to foreskin irritation and another experienced pump-related issues. Conclusions: The Mini-Jupette in tandem with an IPP is a safe and effective treatment option for men with severe ED experiencing sexually related incontinence as well as SUI post-RP. This is the first report of IPP placement with a Mini-Jupette sling successfully treating foreplay incontinence. Disclosure: Work supported by industry: no. A consultant, employee (part time or full time) or shareholder is among the authors (Antares Pharma, Clarus Therapeutics, Coloplast, Promescent, Viome).